Analysis of Compliance Level of Fishing Activities In The Natuna Sea - Wibowo, Dwi Santoso; Supriatna, Ateng; Tri Hewindati, Yuni (Torani Journal of Fisheries and Marine Science, 2023)
Illegal fishing in Indonesian territorial waters, especially by foreign fishermen, has harmed the Indonesian state financially, because it has contributed greatly in reducing productivity and catches very significantly. It has has also threatened the sustainability of the utilization of Indonesia’s marine fishery resources. Economic losses due to IUUF are not only in the form of state income which reaches the range of Rp. 30 trillion per year, but also the loss of opportunities to utilize fish resources of around 1 million tons of fish each year that can be caught (harvested) by Indonesian fishermen, and what happens is in fact stolen by foreign fishermen. entering Indonesian waters. Foreign fishermen who often enter Indonesian waters, among others, come from Thailand, Vietnam, the Philippines, and Malaysia. To prevent and overcome IUUF activities, one of the steps taken by the Ministry of Maritime Affairs and Fisheries (KKP) of the Republic of Indonesia through the Directorate General of Supervision of Marine and Fishery Resources (DITJEN PSDKP) is to supervise fisheries such as fishing activities in the fisheries management area of ​​the Republic of Indonesia. Supervisory implementation is carried out by the Technical Implementation Unit (UPT) PSDKP. UPT Directorate General of PSDKP in handling its duties is supported by the Marine and Fishery Resources Supervision Unit (PSDKP Satker) and Marine and Fishery Resources Monitoring Post (PSDKP Post) spread throughout Indonesia. In carrying out its duties, the Fisheries Supervisory Vessel may stop, inspect, carry, and detain ships suspected of violating the law to the nearest port for further processing. In addition, based on Law No. 31 of 2004 concerning Fisheries, as amended by Law No. 45 of 2009, in certain cases Fishery Supervisory Vessels, in this case, fishery supervisors or Fisheries Civil Servants Investigators, can also take special actions in the form of drowning. The high level of fishing activity in the Indonesian State Fisheries Management Area 711 must be accompanied by adequate monitoring activities to ensure compliance by business actors, both industrial scale and small fishermen, so that the sustainability of fisheries resources can be maintained.